Effect of Drying Temperatures on Starch-Related Functional and Thermal Properties of Acorn Flours - Correia, P R; Beirão-da-Costa, M L (Journal of Food Science, 2011)
Abstract: The application of starchy flours from different origins in food systems depends greatly on information about the chemical and functional properties of such food materials. Acorns are important forestry resources in the central and southern regions of Portugal. To preserve these fruits and to optimize their use, techniques like drying are needed. The effects of different drying temperatures on starch-related functional properties of acorn flours obtained from dried fruits of Quercus rotundifolia (QR) and Quercus suber (QS) were evaluated. Flours were characterized for amylose and resistant starch (RS) contents, swelling ability, and gelatinization properties. Drying temperature mainly affected amylose content and viscoamylographic properties. Amylograms of flours from fruits dried at 60 °C displayed higher consistency (2102 B.U. and 1560 B.U., respectively, for QR and QS). The transition temperatures and enthalpy were less affected by drying temperature, suggesting few modifications in starch structure during drying. QR flours presented different functional properties to those obtained from QS acorn flours. The effect of drying temperatures were more evident in QR.
Keywords: acorn flours; drying; Functional properties; starch; thermal analysis

Effect of drying temperatures on chemical and morphological properties of acorn flours - Correia, Paula R.; Leitão, António E.; Beirão-da-Costa, Maria L. (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.
Keywords: Acorn (Quercus suber and Quercus rotundifolia); chemical properties; drying; morphology

Effect of drying temperatures on chemical and morphological properties of acorn flours - Correia, Paula R.; Leitão, António E.; Beirão-da-Costa, Maria L. (International Journal of Food Science & Technology, 2009)
Drying curves at diﬀerent temperatures were established for Quercus suber and Quercus rotundifolia fruits. Flours produced by milling fruits dried at diﬀerent conditions were evaluated for colour, starch granules morphology, amylose and sugars content. The drying temperature was positively related to the reducing sugar content and negatively to starch content. The amilose content generally increased with drying temperature and the eﬀect was more evident for the Q. rotundifolia. Results showed that ﬂour colour parameters generally decreased with increased drying temperature. However, the drying temperature does not seem to aﬀect starch morphology. It can also be stated that Q. suber produced darker ﬂours, higher amylose and reducing sugar content, and bigger starch granules. Q. rotundifolia showed a lower level of damaged starch and higher fat and disaccharides content. According to the results, it was possible to conclude that drying temperature exerted marked eﬀects on the properties of acorn ﬂours in both studied species.
Keywords: Acorn (Quercus suber and Quercus rotundifolia); chemical properties; drying; morphology